Physiological Features of Yield Formation of Sunflower Breeding Samples in Arid Conditions of the Ukrainian Steppe - Igor Aksyonov; Marina Kotchnenko (Turkish Journal of Agriculture: Food Science and Technology)
The research methodology was based on determining the soil moisture consumption per unit of photosynthesis productivity, establishing the influence of the moisture consumption coefficient on the productivity of photosynthesis on the yield of sunflower genotypes. The aim of the research was to determine the physiological characteristics of the formation of plant productivity of different sunflower samples and use them in assessing and creating genotypes for cultivation in arid conditions. The conducted investigations allowed to determine physiological factors and properties of plants that determine the level of formation of the weight of seeds of the head and the yield of sunflower. The weight of seeds of the head is determined by the amount of soil moisture consumption per unit of net productivity. Between the indicators of soil moisture consumption per unit of net productivity at the stage of formation of the head - the beginning of flowering, a direct negative correlation interdependence was established. Sunflower varieties with a minimum consumption of soil moisture per unit of net productivity of photosynthesis of 1.01-1.05 m-3 g m-2 per day form in arid conditions of the Steppe of Ukraine the maximum level of weight of seeds of the head of 58.7-78.7 g, which ensures obtaining a high yield within 2.68-3.49 t ha-1. The conducted assessment of genotypes by indicators of soil moisture consumption per unit of net productivity made it possible to create highly productive varieties of sunflower Emelard, Igolya, Orlik.